THE USE OF ELECTRONIC LEARNING MEDIA ON STUDENTS' LEARNING OUTCOMES IN THE FIELD OF FIQH STUDY AT MADRASAH IBTIDAIYAH AL-ITTIHAD JAKARTA PUSAT - Amijoyo, Tarisno; Halim, Abdul (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
At Madrasah Al-Ittihad There is a Study of Fiqh Science. The use of electronic media aims to determine the effect of using electronic media on student learning outcomes in the field of fiqh studies at Madrasah Ibtidaiyah in the 2021-2022 academic year. This type of research uses a survey with a quantitative approach and a correlation type. The research sample was 114 people with simple random sampling technique. The results of the study on the use of electronic media (variable Y) with student learning outcomes in the field of Islamic jurisprudence (variable Y) in the high category, with a mean score of 78.5, and the effect of the use of electronic media (variable X) on student learning outcomes in the field of fiqh studies (variable). Y), with correlation coefficient = 0,846, so 0,846>0,320 in level a 5% and 0,413 in level a 1%. Then the contribution of the influence of the use of electronic media on student learning outcomes in the field of jurisprudence is as follows: D = 0.8462x 100% = 71.55%. In other words, the ability of teachers to use electronic media will affect student learning outcomes, but still pay attention to the use of electronic media owned by students in order to realize better learning achievement.